Pgaruh Model Pembelajaran Search Solve Create And Share (SSCS) dan Problem Based Instruction (PBI) Terhadap Prestasi Belajar dan Kreativitas Siswa - Runtut Prih Utami (Department of Biology Education Faculty of Teacher Training and Education Sebelas Maret Un, 2011)
The aims of this study are to find out: (1) the effect of influence between Search Solve Created and Share learning model and the Problem Based Instruction to the achievement of biology, and (2) the influence between the high creativity students and the low creativity students to the achievement of biology. This research was conducted during May-June 2006, using experimental method by taking two groups randomly. The population of the research is all students in grade X in SMA Negeri 1 Karanganyar 2005/2006. The sample is six classes taken randomly by lottery, the control classes are X1, X4 dan X6, and the experimental classes are X2, X3 and X5. The technique of collection data is using test, documentation, questionaire and observation. The data is analyzed using Anava technique. From the analysis it can be concluded that: (1) there was any influence Search Solve Created and Share learning model and the Problem Based Instruction learning model to the achievement of biology, (2) there was any influence between the high students' creativity and the low students' creativity to the achievement of biology.